Electro-hydraulic actuator tester for fly-by-wire aircrafts - De Lucena, Samuel E. [UNESP] (2007)
An 8051-based microcontroller tester has been designed to reduce troubleshooting time of the Electro-Hydraulic Actuators (EHA) installed in fly-by-wire aircrafts. The tester algorithm first evaluates EHA pressure and position sensor signals to emit either a pass or fail message. The evaluation is based on predefined ranges of EHA pressure and position signals. Next, the instrument tests the EHA response capability - a way of dynamic response evaluation, again issuing a suitable response. The instrument proved to be reliable after being successfully evaluated in laboratory and in a real model test airplane. © 2007 IEEE.